The psychological and emotional state of patients with type 2 diabetes mellitus on the background of excessive body weight - Velichko, V. I.; Nikitina, V. I.; Said, E. V.; Amirova, A. Yu. (Journal of Education, Health and Sport, 2017)
In the work, we studied the parameters of the psychological and emotional state of patients with type 2 diabetes mellitus on the background of excessive body weight. Psychological and emotional state studies were conducted using the Patient Health Questionnaire-PHQ-9, questionnaire the hospital scale of anxiety and depression (HADS). A comparison of the frequency of occurrence of anxiety-depressive disorders and the study of the degree of their severity in the patients under study. The study revealed that negative changes in the indicators of psychological and emotional state in patients with type 2 diabetes are six times more likely than in healthy people.